Formation of Research Competence of the Future Primary School Teacher - Nagymzhanova, Karakat; Beisenbayeva, Aigul; Feizuldayeva, Saltanat; Zhiyentaeyva, Begaim; Abilova, Batzhamal (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
Pedagogical research competence has recently become an essential educational outcome in future teacher training to conduct social and professional activities. The purpose of this study is to identify the state and means of development of research activity of future primary schoolteachers. A questionnaire survey of students at a pedagogical university was conducted. The conditions for the formation of the specified competence in the system of modern education of Kazakhstan are offered. During this empirical research, the level of students’ mastering of skills, which are the basis of research competence, was established. Future teachers at the stage of training need to receive proper research experience. The practical significance of this lies in the development of methodological recommendations, covering key, theoretical information about the features of pedagogical-research competence and its means of development, in the context of training future primary schoolteachers.